Reduced activity of Arabidopsis chromosome-cohesion regulator gene CTF7/ECO1 alters cytosine methylation status and retrotransposon expression - Bolaños Villegas, Pablo Alberto (2015)
ORCID IDs: 0000-0003-1729-0561 (P.B.-V.); 0000-0003-3459-1331 (G.-Y.J.)